Calibration for Pulsed Electroacoustic Space Charge Measurement Using Frequency-Resolved Analysis - Li, Xiaoxin; Kawashima, Tomohiro; Murakami, Yoshinobu; Hozumi, Naohiro; Morshuis, Peter (IEEE Transactions on Dielectrics and Electrical Insulation, 2025)
The pulsed electroacoustic (PEA) technique for measuring space charge in electrical insulation systems requires a proper calibration procedure. Most calibration techniques require the test specimen to be space-charge-free when the calibration voltage is applied. In practice, however, this requirement may be hard to fulfill. Either some unknown space charge may be present in the test specimen or space charge is built up during the calibration procedure. Both situations lead to improper calibration. To overcome this problem, a technique was developed that discriminates between space charge and the electrode signal related to the calibration voltage. This technique makes use of the fact that while part of the electrode signal follows a change in the calibration voltage almost instantaneously, the contribution of the space charge will follow with some delay. In the frequency domain, this results in an imaginary component in case space charge being present. This allows introducing a procedure that allows proper calibration, even in the presence of a changing space charge distribution during calibration. In this article, the validity of the proposed method is verified by simulation and practical experiment, in which the calibration signal is acquired at high frequency where the imaginary component is almost zero and the signal can be seen as free from space charge.